The role of women in the current labour market - Sedláčková, Jana (Univerzita Pardubice, 2009)
This paper focuses on the role of women in the current labour market. Its aim is to demonstrate their unequal position in the both Czech and English workplace and to show the main reasons causing such situations. It provides the reader with the historical development of women's positions in European society; discrimination in the workplace and the analysis of the current labour market.
Keywords: Gender; Labour Market; The Czech Republic; Great Britain; Gender; pracovní trh; Česká Republika; Velká Británie